Anthropometry and Biomotor of Various position Young Football Athletes: does it affect performance? - Annas, Mohamad; Soegiyanto, Soegiyanto; Hidayah, Taufiq; Hartono, Mugiyo; Setyawati, Heny; S, Adi (Jurnal Kesehatan Masyarakat, 2024)
This study aims to determine the relationship between anthropometry and biomotor on the performance of young soccer athletes. The sample is football academy athletes from Central Java. The sample is 221 Football Academy Athletes. This research uses total sampling. The selected sample is the 12-year-old group. Researchers directly collected data on the subject. All samples have filled the willingness to be studied. In anthropometry, researchers collected data on height, weight, head circumference, arm circumference, abdominal circumference, thigh circumference, chest circumference, arm length, and leg length. Biomotor components were measured using flexibility, leg strength, agility, coordination, and a 12-minute and 20-meter run. Performance was measured by observation from the researcher. Researchers see the appearance of players in a match The data obtained is processed using descriptive statistics, which include: minimum, maximum, mean, and std. Deviation. Researchers processed the data using normality, homogeneity, and correlation tests—statistical tests using SPSS version 22. There is an anthropometric and bio-motor relationship to the performance of young soccer athletes. There are positively correlated in all positions (Forwards, Backs, Goalkeepers, Centers). The researcher suggested that other groups accomplish further research with a broader range of subjects. Efforts to advance the football sector are expected to continue to be pursued to promote sports development.